2013
DOI: 10.1037/a0030266
|View full text |Cite
|
Sign up to set email alerts
|

Can cognitive models explain brain activation during word and pseudoword reading? A meta-analysis of 36 neuroimaging studies.

Abstract: Reading in many alphabetic writing systems depends on both item-specific knowledge used to read irregular words (sew, yacht) and generative spelling-sound knowledge used to read pseudowords (tew, yash). Research into the neural basis of these abilities has been directed largely by cognitive accounts proposed by the dual-route cascaded and triangle models of reading. We develop a framework that enables predictions for neural activity to be derived from cognitive models of reading using 2 principles: (a) the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

55
416
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 321 publications
(509 citation statements)
references
References 164 publications
55
416
6
1
Order By: Relevance
“…The evidence shows that they are, even during tasks that do not require meaning to be accessed, such as reading aloud/silently and lexical decision (judging whether a letter string is a word). Relative to reading pseudowords (pronounceable but meaningless letter strings), reading words activates brain regions such as left angular and middle temporal gyri, which are likely involved in semantic processing (Taylor, Rastle, & Davis, 2013;Taylor et al, 2014a). Furthermore, neurophysiological experiments reveal that this differential response to meaningful versus meaningless items can occur as early as 160-200ms post-stimulus onset (Carreiras, Armstrong, Perea, & Frost, 2014).…”
Section: Neuroimagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence shows that they are, even during tasks that do not require meaning to be accessed, such as reading aloud/silently and lexical decision (judging whether a letter string is a word). Relative to reading pseudowords (pronounceable but meaningless letter strings), reading words activates brain regions such as left angular and middle temporal gyri, which are likely involved in semantic processing (Taylor, Rastle, & Davis, 2013;Taylor et al, 2014a). Furthermore, neurophysiological experiments reveal that this differential response to meaningful versus meaningless items can occur as early as 160-200ms post-stimulus onset (Carreiras, Armstrong, Perea, & Frost, 2014).…”
Section: Neuroimagingmentioning
confidence: 99%
“…In both a meta-analysis and an empirical study, Taylor et al (2013;2014a) found that exception words activate left inferior frontal gyrus more than regular words. This may reflect the retrieval and selection of semantic knowledge (Graves, Desai, Humphries, Seidenberg, & Binder 2010), or selection between the multiple pronunciations that are possible for exception words (Taylor et al, 2013;2014a).…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a large body of research using meta‐analytical approaches in the field of single‐word recognition (Jobard, Crivello, & Tzourio‐Mazoyer, 2003; Martin, Schurz, Kronbichler, & Richlan, 2015; Taylor, Rastle, & Davis, 2013; Turkeltaub, Eden, Jones, & Zeffiro, 2002). In general, our results were in agreement with previous findings that ventral regions, such as the VOT, MTG, and IFG, are activated during single word processing.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that these meta‐analysis studies included orthographic, phonological, and semantic tasks for single word recognition and contained both silent and oral reading. Consequently, researchers have also found “dual routes” for single word reading (e.g., Coltheart, Rastle, Perry, Langdon, & Ziegler, 2001; Jobard et al., 2003; Taylor et al., 2013). This dual‐route system is comprised of a dorsal phonological pathway (i.e., the STG, SMG, and opercular part of the IFG) and a ventral lexical‐semantic pathway (i.e., the VOT, MTG, and triangular part of the IFG) among left perisylvian regions.…”
Section: Discussionmentioning
confidence: 99%